Raznovrstnost tipov ektomikorize v bukovih sestojih različno onesnaženih gozdnih ploskev - Al Sayegh-Petkovšek, Samar (Zbornik gozdarstva in lesarstva, 2004)
Types of ectomycorrhizae were identified by the mycobioindication method and biodiversity was assessed in soil cores from differently polluted beech forestresearch plots in the period 1998 - 2001. Forest research plots were situated in the vicinity of thermal power plants (polluted plots: Zavodnje - Prednji vrh and Zasavje - Dobovec) and in unpolluted areas (in the vicinity ofKočevska Reka: Preža and Moravške gredice). Eighty-eight different types of ectomycorrhizae were determined from a total of 95,044 root tips. Biodiversityindices (Shannon- Weaver index of diversity, species richness and equitability) were estimated. In soil cores from polluted areas no decrease inbiodiversity was determined. Consequently, it can be concluded that high biodiversity reflects good health status of beech forest in Slovenia.
Keywords: biodiverziteta; bukovi sestoji; ektomikoriza; Fagus sylvatica